The Burden of Uterine Fibroids for African-American Women: Results of a National Survey - Stewart, Elizabeth A. (Mary Ann Liebert, Inc., 2013)
BACKGROUND: Uterine fibroids have a disproportionate impact on African-American women. There are, however, no data to compare racial differences in symptoms, quality of life, effect on employment, and information-seeking behavior for this disease. METHODS: An online survey was conducted by Harris Interactive between December 1, 2011 and January 16, 2012. Participants were U.S. women aged 29–59 with symptomatic uterine fibroids. African-American women were oversampled to allow statistical comparison of this high-risk group. Bivariate comparison of continuous and categorical measures was based on the t-test and the Chi-squared test, respectively. Multivariable adjustment of risk ratios was based on log binomial regression. RESULTS: The survey was completed by 268 African-American and 573 white women. There were no differences between groups in education, employment status, or overall health status. African-American women were significantly more likely to have severe or very severe symptoms, including heavy or prolonged menses (RR=1.51, 95% CI 1.05–2.18) and anemia (RR=2.73, 95% CI 1.47–5.09). They also more often reported that fibroids interfered with physical activities (RR=1.67, 95% CI 1.20–2.32) and relationships (RR=2.27, 95% CI 1.23–4.22) and were more likely to miss days from work (RR=1.77, 95% CI 1.20–2.61). African-American women were more likely to consult friends and family (36 vs. 22%, P=0.004) and health brochures (32 vs. 18%, P<0.001) for health information. Concerns for future fertility (RR=2.65, 95% CI 1.93–3.63) and pregnancy (RR=2.89, 95% CI 2.11–3.97) following fibroid treatments were key concerns for black women. CONCLUSIONS: African-American women have more severe symptoms, unique concerns, and different information-seeking behavior for fibroids.